Chciwość czy kultura chciwości? Dyskusje nad źródłami kryzysu finansowego - Sójka, Jacek (Człowiek i Społeczeństwo, 2014)
Greed as an excessive desire for wealth returned as a popular catchword after the fall of Lehman Brothers in 2008. Because it was only the beginning of the global financial crisis, the notion of greed has been present in public discourse since that time. A legitimate question arises to what extent it could have really contributed to economic instability. But equally important are the questions of semantics. Of course, the notion of greed has its ancient roots and has been always present in religious writings and philosophical works, but today’s use of this notion requires an analysis. What do we mean when we say “greed”? What do we want to achieve (pragmatic aspect), and what are the motives of those writers who include greed into their diagnoses of economic downturns? The major claim of this article is that greed as an individual desire cannot be a proper explanation of the crisis. More important factors are the political and social mechanisms, esp. the role of the regulators of the mortgage industry in the US. Sociological analysis of that industry, which triggered the whole crisis, shows that the crisis was not an example of the excess of the free market and deregulation but rather something created by the politicians. Paradoxically an analysis of the systemic social and political factors which had led to the crisis allow us to reflect on greed as a notion which is a part of the so-called culture of excess – characterized, among others, by the process of the “democratization of desires”.